Comparison of scanning laser ophthalmoscopy and high-definition optical coherence tomography measurements of optic disc parameters. Issue 4 (9th February 2012) - Foo, Li-Lian; Perera, Shamira A; Cheung, Carol Y; Allen, John C; Zheng, Yingfeng; Loon, Seng-Chee; Wong, Tien Y; Aung, Tin
Abstract : Objective: To investigate the agreement between scanning laser ophthalmoscopy (Heidelberg retinal tomograph 3; HRT-3) and high-definition optical coherence tomography (HD–OCT) for measurements of optic nerve head (ONH) parameters. Methods: As part of a population-based cross-sectional study, 913 consecutive Chinese subjects aged 40 years and older underwent HRT-3 and HD–OCT imaging of the ONH after pupillary dilation. Limits of agreement (LOA) derived from Bland–Altman analysis were calculated for ONH measurements. Results: The mean age (±SD) of study participants was 54.2±7.2 years and 52.0% were men. The two instruments showed no difference in mean optic disc area measurements (1.98±0.37 for HD–OCT vs 1.98±0.39 mm for HRT-3, p=0.95). HD–OCT showed smaller rim area (1.29±0.24 vs 1.46±0.27 mm, p<0.001), but bigger cup-related parameters (p<0.001 for all) than HRT-3. The highest correlations between the instruments were observed for cup volume (r 2 =0.74, p<0.001) and disc area (r 2 =0.62, p<0.001). The correlations for cup-to-disc ratio (CDR), vertical CDR and rim area were lower (r 2 =0.59, 0.48 and 0.24, respectively, p<0.001 for all). The Bland–Altman plots demonstrated significant proportional bias for differences in all ONH parameters (p<0.01 for all), with LOA greater for disc-related parameters (0.98–1.0) than cup-related parameters (0.26–0.50). Conclusions: There are substantial disagreements between HRT-3 and HD–OCT in ONH measurements. Although optic disc area measurements were similar, HD–OCT underestimates the rim area and overestimates cup parameters compared with HRT-3.